REBT Approach Group Counseling Against Student Academic Anxiety - Rachel Veronika; Deviana Arleni; Eva Yuliani; Sevira Resiyanti (Penerbit Hellow Pustaka, 2024)
The problem that students often experience is academic anxiety. Symptoms of academic anxiety raised by students include: worrying about not being able to complete assignments according to the collection period that has been carried out and anxiety if they get unsatisfactory end-of-semester exam scores. These symptoms arise due to students' irrational beliefs. Group counselling of the REBT approach in its focus is to transform individual irrational beliefs into rational ones. Group counseling using the REBT approach can be carried out on students whose goal is that after participating in group counseling service activities, students can feel more relieved, have better conditions, and they can understand how to control the academic anxiety they experience. With this goal, REBT group counseling is considered effective in overcoming students' academic anxiety.